EKSISTENSI GURU PROFESIONAL DALAM MENGAKOMODASI SEKOLAH - Asnita,; Rosdiana, (Inspiratif Pendidikan, 2023)
The subject matter of this research is about how the existence of professional teachers in accommodating schools at SDIT Azzahrah Gowa, Samata Village, Somba Opu District, Gowa Regency. This research aims to 1) Knowing the performance of professional teachers at SDIT Azzahrah Gowa, 2) Describe professional teachers accommodating schools in SDIT Azzahrah Gowa, and 3) Find the principal's policy in forming professional teachers in SDIT Azzahrah Gowa. This type of research is a descriptive qualitative research that is contained in participant observation which produces data and information in the form of words or sentences that come from the object of observation, using a pedagogical and sociological approach that explains descriptively and has primary data sources and secondary data. Data collection methods are observation and interview methods. The data processing and analysis techniques use data reduction, data presentation, and data verification and use triangulation techniques as a submission of data validity both technique, time and source triangulation. The results of the interviews showed that 1) The existence of professional teachers in schools is very helpful in improving the quality of education, because the principal conducts training related to professional teachers in schools and teachers show complete administration in learning, 2) The application of professional teachers carried out by teachers in schools is by fulfilling the tools of teaching needs, attendance, making academic calendars, working meetings with other teachers, and proven by attending trainings to improve professional teachers in accommodating schools, 3) Reporting the existence of professional teachers in accommodating schools is evidenced by the improved performance of teachers in making lesson plans, timely attendance to school, good information systems, teacher leadership shows good examples, and conducts evaluations in a timely manner. The implication of the research is that teachers should be professional in carrying out their duties as educators in order to be able to make a good contribution in accommodating schools and it is hoped that this research can be an input and reference for further research